Modulation of Neuritogenesis by a Protein Implicated in X-Linked Mental Retardation - Jiao, Xinfu (Society for Neuroscience, 2009)
Posttranscriptional regulation is an important control mechanism governing gene expression in neurons. We recently demonstrated that VCX-A, a protein implicated in X-linked mental retardation, is an RNA-binding protein that specifically binds the 5′ end of capped mRNAs to prevent their decapping and decay. Previously, expression of VCX-A was reported to be testes restricted. Consistent with a role in cognitive function, we demonstrate that VCX-A is ubiquitously expressed in human tissues including the brain. Moreover, retinoic acid-induced differentiation of human SH-SY5Y neuroblastoma cells promoted the accumulation of VCX-A in distinct cytoplasmic foci within neurites that colocalize with staufen1-containing RNA granules, suggesting a role in translational suppression and/or mRNA transport. Exogenous expression of VCX-A in rat primary hippocampal neurons, which normally do not express the primate-restricted VCX proteins, promoted neurite arborization, and shRNA-directed knockdown of the VCX genes in SH-SY5Y cells resulted in a reduction of both primary and secondary neurite projections upon differentiation. We propose that the cap-binding property of VCX-A reflects a role of this protein in mRNA translational regulation. In support of this hypothesized role, we demonstrate that VCX-A can specifically bind a subset of mRNAs involved in neuritogenesis and is also capable of promoting translational silencing. Thus, VCX-A contains the capacity to modulate the stability and translation of a subset of target mRNAs involved in neuronal differentiation and arborization. It is plausible that defects of these functions in the absence of the VCX genes could contribute to a mental retardation phenotype.